(untitled) (المجلة العربية للعلوم و نشر الأبحاث, 2018)
Museums are peoples’ memory and an effective tool for preserving identity, much more they are considered as space where the remnants of time and the treasures of the ancestors are gathered. Preventing this memory from being destroyed or let to forgetting, it must be revitalized by inventing effective ways to attract more visitors allowing them to be in touch with what their ancestors have left as exploits that reflect their way of living and narrate their heroisms. If antiques and collectibles are the only way to allow visitor to enter such spaces and getting the pleasure to see them, and if the exhibition hall is the only space to be visited among other spaces, how will it be possible, then, for the administration to take advantage of this opportunity to effectively invest in the museum and to devote its culture. Are there any specific rules that should be followed to make the museum exhibition a success, or is it a matter of routine procedures that any ordinary staff member can do it without recourse to experts, technicians or artists. Museum of all kinds are seeking to collect more collectibles either by buying, exchanging, offering as a gift or on loan, all this in order to fill the exhibition gallery, hence owning a great number of these collectibles is not enough to bring significant number of visitors, more than that; the value of such masterpiece will diminish if it remains isolated and maybe it will be damaged. For that, it’s the department duty to work hard for applying a set of scientific and studied rules which will add an aesthetic to the collectibles and to the space as a whole and thus it’ll raise the curiosity of viewers. Based on this, we will try to show the importance of the museum presentation in activating the museum’s culture.